Probiotic potential of Phocaeicola coprocola in modulating learning and memory behaviors in the honeybee model - Xu, Mengqi; Zhang, Xiaohan; Luo, Xi; Zhou, Guanzhou; Zhang, Nana; Chi, Xiaoyan; Ren, Rongrong; Peng, Lihua; Sun, Gang; Yang, Yunsheng (Frontiers in Microbiology, 2025)
IntroductionGut microbial therapy has emerged as a prominent research topic for brain function and disorders. The depletion of Phocaeicola coprocola has been reported in various brain-related conditions, suggesting its possible neuroprotective and cognitive benefits. However, its functional roles and underlying mechanisms remain poorly understood.MethodsWe evaluated the effects of P. coprocola on cognitive performance using the honeybee (Apis mellifera) as a novel model for the microbiota–gut–brain axis. Honeybees with a standardized gut microbiota served as the control group, while those supplemented with P. coprocola comprised the treatment group. Olfactory learning and memory were assessed using classical conditioning assays. Gut microbial composition was analyzed using full-length 16S rRNA gene sequencing based on PacBio SMRT technology, and metabolic profiling was conducted using untargeted LC–MS/MS analysis.ResultsP. coprocola supplementation significantly improved cognitive performance, with learning success rates of 74.13% in the treatment group versus 50.85% in controls (p = 0.0093). This intervention also led to increased gut diversity (Shannon index, p = 0.0079). Metabolomic analysis revealed substantial alterations in intestinal lipid metabolism, particularly in glycerophospholipid pathways (p = 0.0002). Furthermore, the increase in protective lipid molecules, such as phosphatidylcholine, glycerophosphocholine, and glycerophosphoethanolamine, was strongly correlated with Gilliamella apicola, Bifidobacterium asteroides, and Bombella apis.DiscussionP. coprocola has potential as a probiotic candidate for modulating cognition-related processes via gut microbial and metabolic interactions. Moreover, the honeybee model offers a valuable platform for preclinical investigation of microbiota-gut-brain relationships and probiotic screenin.